Balancing Interests in Responding Pandemic Covid-19 in Palembang: The Policy Networks Analysis - Eti Yusnita; Siti Anisyah (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research examines the political economy of policies and policy networks in Palembang policies to handle pandemic. So far, policy studies with a political nature have always placed policy products as the result of the compromise based on